This Analisis Faktor-faktor yang Mempengaruhi Keputusan Pembelian iPhone: Kualitas Produk, Harga, Promosi, Citra Merek, dan Gaya Hidup, Cilacap, Purbalingga, Banyumas, iPhone - Subagyo, Dimas Apryansyah; Rachmawati, Erny; Kusbandiyah, Ani; Fakhruddin, Iwan (Universitas Muhammadiyah Pontianak, 2026)
This study analyzes the influence of product quality, price, promotion, lifestyle, and brand image on consumers’ purchasing decisions for iPhones in the Calingmas region (Cilacap, Purbalingga, and Banyumas). A quantitative survey was conducted with 130 iPhone users selected through accidental and snowball sampling. Data were collected using a Likert-scale questionnaire and analyzed with multiple linear regression in SPSS 27. The findings reveal that product quality, price, and brand image significantly affect purchasing decisions, whereas promotion and lifestyle do not. These results highlight the dominant role of functional value and brand strength in shaping consumer decisions.